Integrated WGCNA and PPI Network to Screen Hub Genes Signatures for Infantile Hemangioma - Xu, Miao; Ouyang, Tianxiang; Lv, Kaiyang; Ma, Xiaorong (Frontiers in Genetics, 2021)
Background Infantile hemangioma (IH) is characterized by proliferation and regression. Methods Based on the GSE127487 dataset, the differentially expressed genes (DEGs) between 6 months, 12 months or 24 months and normal samples were screened, respectively. STEM software was used to screen the continued up-regulated or down-regulated in common genes. The modules were assessed by weighted gene co-expression network analysis (WGCNA). The enrichment analysis was performed to identified the biological function of important module genes. The area under curve (AUC) value and protein-protein interaction (PPI) network were used to identify hub genes. The differential expression of hub genes in IH and normal tissues was detected by qPCR. Results There were 5785, 5002 and 4712 DEGs between 6 months, 12 months and 24 months and normal tissues. We found 1218 DEGs were up-regulated or down-regulated expression simultaneously in common genes. They were identified as 10 co-expression modules. Module 3 and module 4 were positively or negatively correlated with the development of IH, respectively. These two module genes were significantly involved in immunity, cell cycle arrest and mTOR signaling pathway. The two module genes with AUC greater than 0.8 at different stages of IH were put into PPI network, and five genes with the highest degree were identified as hub genes. The differential expression of these genes was also verified by qRTPCR. Conclusion Five hub genes may distinguish for proliferative and regressive IH lesions. The WGCNA and PPI network analyses may help to clarify the molecular mechanism of IH at different stages.